Nilai budaya dalam cerita rakyat Jawa Tengah sebagai alternatif materi ajar sekolah dasar - Safa Rizki San Nugroho; St Y Slamet; Septi Yulisetiani (Didaktika Dwija Indria, 2024)
Folklore is a literary work that incorporates cultural values. The findings of this study provide cultural value data that may be used as alternative teaching material in primary schools. The goal of this study is to provide instructors with an alternate teaching material that will reinforce cultural values in primary schools. This research method takes a qualitative approach and collects data using a methodology known as literary studies. The Central Java provincial language center issued a book titled Central Java folklore in three languages, which served as the focus of this research. The researcher picked 11 folktales from the novel. The findings of cultural values in the folklore book yielded 15 cultural values of human relationship with God, 8 cultural values of human interaction with nature, 23 cultural values of human relationship with others, and 24 cultural values of human relationship with job and self.